2007
DOI: 10.1080/00048670701689428
|View full text |Cite
|
Sign up to set email alerts
|

Management of Antipsychotic-Induced Weight Gain: Prospective Naturalistic Study of the Effectiveness of a Supervised Exercise Programme

Abstract: Bodyweight and metabolic risk profile in patients receiving atypical antipsychotic medications can be effectively managed with a weight control programme including physical activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
82
1
6

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(94 citation statements)
references
References 50 publications
5
82
1
6
Order By: Relevance
“…15,16 In addition to resistance training, previous studies of patients with schizophrenia have used a combination of aerobic and resistance exercises in the same session, which is known as concurrent exercise. 5,17,18 Marzolini et al examined concurrent exercise twice a week for 12 weeks among patients with schizophrenia and found that this type of training improves general mental health and generally increases muscle strength. 5 Scheewe et al recently found similar results, with improvement of schizophrenia symptoms after 6 months of concurrent training.…”
Section: Introductionmentioning
confidence: 99%
“…15,16 In addition to resistance training, previous studies of patients with schizophrenia have used a combination of aerobic and resistance exercises in the same session, which is known as concurrent exercise. 5,17,18 Marzolini et al examined concurrent exercise twice a week for 12 weeks among patients with schizophrenia and found that this type of training improves general mental health and generally increases muscle strength. 5 Scheewe et al recently found similar results, with improvement of schizophrenia symptoms after 6 months of concurrent training.…”
Section: Introductionmentioning
confidence: 99%
“…Comprehensive weight management programmes, including diet, exercise and counselling on lifestyle modifications, can also prove helpful in reducing weight, as shown by a naturalistic study and an RCT [Kwon et al 2006;Poulin et al 2007]. However, another naturalistic study showed no significant outcomes following a similar nurse-led programme in patients with schizophrenia spectrum disorders [Ohlsen et al 2004].…”
Section: Description and Discussion Of Studiesmentioning
confidence: 99%
“…Cinq études ont inclus le profil lipidique comme mesure d'effet (29,4 %). Seule l'étude de Poulin et al (2007) relève un impact différentiel de leur programme sur le profil lipidique des patients. Après 18 mois, leurs résultats démontrent une amélioration du profil lipidique de leurs participants en ce qui a trait au cholestérol total, du cholestérol LDL et HDL et sur le taux de triglycérides.…”
Section: Variables Anthropométriquesunclassified